Effect of Feeding Diets Combining Whole-Grain Paddy Rice and High Levels of Fat on Broiler Chicken Growth - Nanto, Fumika (J Poult Sci, 2016)
Previously, we showed that the growth of chicks fed a diet containing 43% whole-grain paddy rice and 10% soybean oil was retarded relative to a control group fed a corn-based diet containing 6% soybean oil. However, feeding chicks with 43% whole-grain paddy rice containing 6% soybean oil resulted in normal growth. It is possible that the observed growth retardation was caused by the high soybean oil content or resulted from the combination of whole-grain paddy rice and the high level of soybean oil which was added to the diet to maintain the overall energy content. The present study was therefore carried out to identify the reasons for the observed growth retardation. Thirty-six chicks (0-day-old) were divided into six equal-sized groups that were fed one of the following six experimental diets ad libitum for 28 d: two kinds of dehulled rice-based diets containing 5% or 10% soybean oil (DS5% or DS10%), another three whole-grain paddy rice-based diets containing 10% soybean oil, corn oil, or rendering oil (WS10%, WC10%, WR10%, respectively), and a WS10% diet supplemented with vitamin B(12), methionine and ethoxyquin. The body weight gain of groups fed the WS10% and WC10% diets was significantly lower than the weight gain of birds fed the DS5% diet (control). In addition, the liver of birds fed the WS10% and WC10% diet exhibited significantly higher lipid peroxidation than that of the control group. In comparison, supplementation of the WS10% diet with vitamin B(12), methionine and ethoxyquin dramatically improved growth and hepatic oxidation status. These results indicate that diets combining whole-grain paddy rice and high levels of soybean and corn oil adversely affect performance, presumably via lipid peroxidation in the liver.